Kesantunan Berbahasa Pekerja di Gudang Sango-Sango (Rumput Laut) Ballo 1 Kabupaten Takalar - Isramia Dewi Putri M; Andi Agussalim Aj; Nurhusna Nurhusna (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract. The purpose of this study is to describe the politeness principles and politeness violations in Makassar language in worker interactions at the Sango-Sango (Seaweed) Warehouse Ballo 1, Takalar Regency. This type of research is qualitative descriptive research. The method used is the collection of research data is recording, see fleely involved competent, and recording. Data analysis in this study begins with describing the data in the form of recorded conversation data in the field, the next process is indentifying the data, and recuding words. The validity of the data was obtained from the triangulation process using the technique of triangulation of data sources, observers and theories. The results of this study indicate that (1) the politeness principle consists of the maxim of wisdom and agreement, the maxim of generosity, the maxim of humility, the maxim of praise, the maxim of agreement and the maxim of sympathy. (2) violation of politeness maxims in the form of (a) violation of two maxims, namely the maxim of wisdom and maxim of agreement (b) violation of three maxims, namely the maxim of wisdom, the maxim of sympathy, and the maxim of agreement. Keywords: Politeness in Language, Politeness Principles, Violation of Maxims, Workers.